A randomized phase II trial of concurrent chemoradiation with two doses of radiotherapy, 60 Gy and 66 Gy, concomitant with a fixed dose of oral vinorelbine in locally advanced NSCLC. Issue 2 (May 2017) - Hansen, Olfred; Knap, Marianne M.; Khalil, Azza; Nyhus, Christa H.; McCulloch, Tine; Holm, Bente; Brink, Carsten; Hoffmann, Lone; Schytte, Tine
Abstract: Introduction: In order to test the best performing radiation dose with a convenient chemotherapy schedule of an oral formulation of radio-sensitizing vinorelbine in inoperable locally advanced non-small cell lung cancer (NSCLC), we performed a randomized phase II trial based on a "pick the winner" design. Methods: After 2 cycles of neoadjuvant chemotherapy, 117 patients with NSCLC stage IIB–IIIB in performance status 0–1 were randomized to radiotherapy 60 Gy/30 fractions or 66 Gy/33 fractions concurrent with a fixed dose of oral vinorelbine 50 mg administered 3 times weekly. The primary endpoint was local progression free interval. A scheduled FDG-PET-CT-scan was performed 9 months after randomization. The study was registered at ClinicalTrials.gov (NCT 00887783). Results: Both arms were well tolerated. The local progression free interval at 9 months was 54% in the 60 Gy arm and 59% in the 66 Gy arm (log rank test p = 0.55). There was no statistically significant difference in overall survival. The median survival was 23.3 and 23.7 months in the 60 and 66 Gy arm, respectively. No significant difference in toxicity was observed. Conclusion: Both 60 and 66 Gy administered concomitant with oral vinorelbine showed similar local control and overall survival, and was well tolerated. The pick the winner design choose 66 Gy as the winning arm.